Optimising tractor mechanisation in Malaysian agriculture: challenges, cost reduction strategies, and sustainability practices - Rizal, Mohamad Syazwan; Bakar, Muhammad Aliuddin; Ismail, Nur Amalina; Syahlan, Syahrizan; Zulkifli, Farahida (Universiti Teknologi MARA, Sabah, 2025)
Agriculture mechanisation, mainly through the use of tractors, significantly enhances land cultivation efficiency and crop yields, but the high operational and maintenance costs present financial challenges for farmers. The primary issue of mechanisation in Malaysian agriculture is the high cost and frequent breakdowns of tractors due to age, wear and tear, irregular maintenance, and improper usage, which negatively impact productivity and increase environmental footprint. This study analysed current practices and operational challenges in Malaysian tractor mechanisation and identified effective strategies for reducing costs among stakeholders. Using qualitative approach, the research conducted semi-structured interviews with six respondents from various companies. It employed thematic analysis to identify key themes of mechanisation challenges and cost-reduction strategies. The findings revealed that significant challenges include human factors, technical issues, maintenance and repair issues, operational complexity and environmental impacts. Strategies to reduce costs include regular maintenance, timely service, employment of skilled driver, and proper road conditions. Adopting proactive maintenance strategies, training skilled operators, and implementing energy-efficient technologies are recommended to reduce operational costs and enhance sustainability in Malaysian agriculture.